Amphibious mudskipper populations are genetically connected along coastlines, but differentiated across water. (10th March 2022) - Corush, Joel B.; Pierson, Todd W.; Shiao, Jen‐Chieh; Katayama, Yukitoshi; Zhang, Jie; Fitzpatrick, Benjamin M.
Abstract: Aim: Specialized life histories can restrict the way that organisms move through the landscape. Some fishes, such as mudskippers in the family Gobiidae, are obligately amphibious and require a terrestrial phase in which adults build burrows and lay eggs in mudflats. To evaluate whether this restricted, out‐of‐water phase might influence population structure in one such mudskipper, we tested whether populations separated by water are more differentiated than those connected along a coastline. Location: South and East China Seas. Taxon: Periophthalmus modestus (family: Gobiidae, subfamily: Oxudercinae) (Cantor 1842). Methods: We collected 236 individuals from 10 locations around the East and South China Seas. We used a targeted capture sequencing method, RADcap, to call SNPs from 365 loci. We used multiple spatial and population genetics analyses and coalescent models to address the contemporary and historic biogeography of the species. Results: The observed levels of genetic variation and population structure show populations of P. modestus are connected across large distances of continuous coastline and small spans of water. Restricted long‐distance dispersal across deep water has resulted in fragmentation of populations. We recovered no signal of isolation by distance, but instead, found genetic differentiation associated with regional groupings separated by large expanses of water. Main conclusions: A limited dispersal phase significantly affects population structure in this amphibious fish. The restrictive amphibious life history may be a key factor in the present‐day distribution and population structure of P. modestus . Interactions between organismal life history and geography are critical for explaining the population genetic structure of a species.